Thoughts of the Turkic peoples in the Chinese scientific sources - Dossymbekova, R O (Journal of Oriental Studies, 2016)
This article explores the ideas of Chinese researchers about the history , culture , customs and traditions of the Turkic peoples . Аnalyzes the origin of Turkic peoples in the Chinese sources on the basis of research scientists and philosophers.